Filosofi Hijau Pada Selogan "Tioq Tata Tunaq" Kabupaten Lombok Utara - Satria Efendi; Muhammad Sukri (Cordova Journal, 2025)
Apart from being a medium of communication, language also has various functions, one of them as a suggestion tool. There are various multi-disciplines related to language, such as sociolinguistics, psycholinguistics, and so on. There is also the term Eco-linguistics which connects the influence of language with the human biological environment. The slogan "Tioq Tata Tunaq" in North Lombok is the object of the researcher's study in this paper. It is felt that the slogan has a philosophical view of environmental preservation. Until now, there has been no research related to the philosophical content of the slogan "Tioq Tata Tunaq" related to environmental conservation. Therefore, the researcher has studied the slogan using an Eco-linguistic theory approach, with a dialectical linguistic method, parsing the discourse contained in each word listed in the "Tioq Tata Tunaq" slogan by finding inter-textual, intra-textual, and extra-textual elements. Besides, it also parses the key morphemes in the slogan. The researcher found that there is a close connection between the slogan "Tioq Tata Tunaq" and the preservation of the biological environment. After analyzing, the researcher found that each key of morpheme in the slogan directs its meaning to matters related to green philosophy (nature conservation). So it can be said that the slogan "Tioq Tata Tunaq" contains the philosophy of preserving nature or the biological environment. Keyword: Eco-linguistics, Tioq Tata Tunaq, Green Philosophy, Language, Natural Environment, Biology